A Synthetic Review of Feedbacks and Drivers of Shrub–Grass Interaction in the Process of Grassland Shrub Encroachment - Huiyang Hou; Haoran Yan; Xue Bai; Yuzhen Zhang; Yanjun Guo; Jianwei Zhou; Shaobo Gao (Plants)
Many grasslands around the world are affected by shrub encroachment. The essence of shrub encroachment into a grassland habitat is a change in the direction and intensity of shrub–grass interactions, which leads to an alteration in the grassland community structure. Recent research progress can be summarized as encompassing the primary factors influencing shrub encroachment and the physical, biological, and chemical ways through which they affect grassland community succession and shrub–grass interactions. The purpose of this study was to explore how shrub–grass interactions and relationships change under the influence of various environmental factors and their impact on grassland communities to provide a theoretical basis for grassland restoration and the management of shrubs within grassland from the perspective of shrub–grass interaction.